Comparative Analysis of The Perceived Qualitative Characteristics of Accounting Information Under IFRS. Evidence from Algeria - Abdelaziz Boumakhlouf; Mahmoud Kebieche (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Questions- What are the perceptions of Algerian accounting professionals regarding the qualitative characteristics of accounting information after International Financial Reporting Standards (IFRS) adoption in financial accounting system (FAS)? Do different accounting professional groups (preparers and external auditors of financial statements) have different perspectives regarding the qualitative characteristics of accounting information after IFRS adoption in FAS? Motivation- The authors consider that there is a need for a comparative analysis between preparers and external auditors of financial statements to gain insights into their distinct perspectives regarding the qualitative characteristics of accounting information after IFRS adoption within the Algerian context. Idea- This paper explores the accounting and auditing professionals' perceptions regarding the qualitative characteristics of accounting information after the adoption of the IFRS in the new FAS in the Algerian context. It also investigates whether this perception differs between preparers and external auditors of financial statements. Data- Data were collected from 59 preparers (accounting services firms) and 56 external auditors (external audit firms) between October and November 2023. Tools- A questionnaire was developed drawing on the conceptual frameworks of the FAS (2007) and IASB (2018). SPSS software was used to analyze the data and to test hypotheses. Findings- The study found that the two groups of professionals have a positive perception regarding the qualitative characteristics of accounting information after IFRS adoption. Contribution- The study provides new insights for Algerian legislators, regulators, practitioners, and academics about the effectiveness of IFRS adoption in supporting the quality of financial reporting.
Keywords: M40; M41; 650; International Financial Reporting Standards (IFRS); financial accounting system (FAS); qualitative characteristics; accounting information; preparers; external auditors